Determination of Shear Wave Velocity Using Multi-channel Analysis of Surface Wave Method and Shear Modulus Estimation of Peat Soil at Western Johore. (2015) - Zainorabidin, Adnan; Said, Mohd Jazlan Mad
Abstract: Shear wave velocity and shear modulus is common for geotechnical and geophysics engineer to the determine interaction of soil dynamic properties. Both of the dynamic properties were often related to dynamic loading such as earthquake, moving traffic, machineries and bomb blasting. The study was conducted at western part of Johore such as Parit Sulong and Pontian where deposition of peat soil were exists and recognised as problematic soils to the engineers. This study was carried out to determine the shear wave velocity of peat soil using Multi-channel Analysis of Surface Wave (MASW) method and estimation shear modulus of peat using empirical formula. To use the empirical formula, the density of peat soil was also needed thus using the peat sampler for every 0.5 meter depth to obtain the density. From the MASW test for both test sites, the shear velocity of peat at Parit Sulong is between 40 m/s and 55 m/s until depth of 1.5 m meanwhile at Pontian, the shear wave velocity between 21 m/s and 67 m/s until 2.5 m depth. Using shear velocity, shear modulus of peat were estimated for Parit Sulong are ranged between 1575 kPa – 3514 kPa and Pontian are ranged between 385 kPa – 5117 kPa. The shear velocity and shear modulus of peat are very low due to the unique characteristics of peat soils compared with other typical soil.